Primary cardiac angiosarcoma with giant cells: A case report of an autopsy - Bihong Zhao; Hui Zhu; L. Maximilian Buja; Rafael A. Garcia (Elsevier, 2020)
Angiosarcomas are malignant tumors originating from the vascular endothelium. Histologically, angiosarcomas typically possess some functional and morphologic features of normal endothelium, with well or poorly formed vascular channels. Primary cardiac angiosarcoma is a very rare but often fatal malignancy. It is the most common sarcoma of the heart and about one-third of patients present with metastatic disease at the time of diagnosis. Since its discovery in 1934, little progress has been made in terms of treatment methods and patient survival. We present here a rare case of right atrial angiosarcoma with numerous giant cells in a young patient who died of a gunshot wound.